La motivación laboral y el desempeño por competencias de colaboradores de la unidad de gestión educativa local de Loreto-Nauta, periodo 2022 - Carranza Gil, Juan Carlos (2023)
The objective is to explain the influence of motivation on the performance by competencies of the collaborators of the local educational management unit of Loreto-Nauta, period 2022. The type of research is of an explanatory level and a quantitative approach, with a non-experimental research design., causal correlational cross-sectional type. The population is finite, it was made up of 91 collaborators of the institution, the technique was the census, non-probabilistic sampling of the intentional type. The technique was a survey, and the instrument was a 10-question questionnaire for the variable work motivation and 50 questions for the variable performance by competencies, with answers on an ordinal scale. The result of the first dimension, performance by competencies, is weakly influenced by the satisfaction of protection and security needs, the second dimension, performance by competencies, is weakly influenced by the satisfaction of social and belonging needs, the third dimension performance by competencies are not influenced by the satisfaction of self-esteem needs and the last dimension, performance by competencies, is very weakly influenced by the satisfaction of self-actualization needs. We conclude that there is a weak positive correlation between work motivation and performance of skills. It can be inferred in the population that work motivation does not greatly influence the performance of the skills of the collaborators of the local educational management unit.